Effect of the uvrD mutation on excision repair. - Kuemmerle, N B (1980)
A pair of related Escherichia coli K-12 strains, one of which contains the uvrD101 mutation, were constructed and compared for ability to perform various steps in the excision repair of deoxyribonucleic acid damage inflicted by ultraviolet radiation. The results of this study indicated: (i) ultraviolet sensitivity in the uvrD101 mutant was greater than that of wild type but less than that measured in an incision-deficient uvrA mutant; (ii) host cell reactivation paralleled the survival data; (iii) postirradiation deoxyribonucleic acid degradation was virtually identical in the two strains; (iv) incision, presumably at the sites of pyrimidine dimers, proceeded normally in the uvrD101 strain; (v) excision of pyrimidine dimers was markedly reduced in both rate and extent in the uvrD101 mutant; (vi) the amount of repair resynthesis was the same in both strains, and there was no evidence of abnormally long repair patches in the uvrD mutant; and (vii) rejoining of incision breaks was slow and incomplete in the uvrD strain. These data suggest that the ultraviolet sensitivity conferred by the uvrD mutation arises from inefficient removal of pyrimidine dimers or from failure to close incision breaks. The data are compatible with the notion that the uvrD+ gene produce affects the conformation of incised deoxyribonucleic acid molecules.